Relationship of Iron Consumption with Anemia in Pregnant Women - Irna Hasanah; Yasmine Adnindya Syafira; Nurmalia Lusida; FATHATUL FUADIYAH; Munaya Fauziah (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2021)
The prevalence of anemia in pregnant women in Indonesia ranges from 20-80%, but in general, many studies show anemia in pregnant women is greater than 50%. In the western part of Indonesia, the area is classified as high, anemia in Aceh is 56.6%, North Sumatra 77.9%, West Sumatra 8.9%, Riau 65.6%, Jambi 74.2%, South Sumatra 58.3, Lampung 60.7%. In pregnancy, anemia can harm maternal and infant morbidity and mortality. In a pregnant state, the supply of iron from food is still not sufficient so that a supplement is needed in the form of blood/Fe added tablets. Because the benefits of Fe tablets are very large for the prevention of anemia in pregnant women. However, there are still many pregnant women who do not consume Fe tablets up to 90 tablets. So that the administration of Fe tablets has not yet reached the target where the central government has set it. The results of Riskesdas in 2013 from 89.1% of pregnant women who consumed Fe tablets, only 33.3% consumed up to 90 Fe tablets as recommended.